Wooden ground heating floor based on ultraviolet aging resistant surface modification process
By setting a high -elastic primer layer on the inside of the glass fiber layer of the wooden floor, and the surface of light solid resin on the surface, combined with the multi -layer bottom paint layer and the paint film layer, it is easy to solve the glass fiber cloth on the surface of the floor surface. The problem of wrinkle or layered problems realize the structural stability of the floor and the improvement of the service life, and at the same time enhance the aging and wear resistance of light resistance.
Patent Information
- Application Number
- CN202420849049.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2034-04-23
Smart Images

Figure CN222407536U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to a floor heating floor, in particular to a wooden floor heating floor based on a surface modification process for resistance to ultraviolet aging. Background Art
[0002] Since wooden floors will be exposed to light for a long time and will be exposed to ultraviolet rays in the light, manufacturers need to use various means to improve the anti-light aging performance of the floor. On this basis, since the medium-alkali glass fiber cloth contains alkaline metal compounds, it can absorb ultraviolet rays in the light, so that when it is covered on the floor surface, it can effectively reduce the color change of the bottom layer of the floor. In addition, users will also wear and impact the surface of the floor during daily activities. The wear and impact phenomenon will easily cause damage to the floor surface and cracking of the paint film, thereby accelerating the cycle of wood moisture absorption and desorption, making the floor more prone to arching, pulling seams, cracking and other damage phenomena, which not only affects the decorative aesthetics, but also reduces the service life of the floor product. After the glass fiber cloth is introduced into the floor surface for paving, it can play a good role in reinforcing the paint film, thereby improving the physical and mechanical properties of the paint film such as tensile strength, bending resistance, hardness, etc., and achieving the enhancement of the paint film. Therefore, how to effectively and reasonably compound the medium-alkali glass fiber cloth with the paint film coating on the floor surface is a very promising research direction.
[0003] However, the existing technical obstacle of laying medium-alkali fiberglass cloth on wooden floor is that wooden floor will shrink when dry and swell when wet due to the influence of external environmental factors such as temperature and humidity. If the manufacturer directly adheres the medium-alkali fiberglass cloth to the floor surface in the conventional way, the wooden floor will directly apply the deformation force to the medium-alkali fiberglass cloth after deformation. However, the medium-alkali fiberglass cloth cannot form synchronous deformation with the floor substrate due to its own toughness and strength, which will cause the two to separate from each other at the bonding interface during use, that is, the medium-alkali fiberglass cloth will wrinkle or delaminate, causing permanent damage to the floor paint film. Under the above limitations, it is difficult for manufacturers to improve the physical and chemical properties of the floor surface by directly bonding the medium-alkali fiberglass cloth to the floor surface.
[0004] Therefore, the existing wooden floor will cause the problem of wrinkling and delamination of the medium-alkali glass fiber cloth after paving the medium-alkali glass fiber cloth. Utility Model Content
[0005] The purpose of the utility model is to provide a wooden floor heating floor based on a surface modification process that is resistant to ultraviolet aging, which can achieve stable laying of glass fiber cloth on the surface of the wooden floor and prevent the glass fiber cloth from wrinkling and delamination caused by deformation of the floor substrate.
[0006] The technical solution of the utility model: a wooden floor heating floor based on a surface modification process resistant to ultraviolet aging, comprising a substrate, the surface of the substrate being provided with a high-elastic primer layer, a glass fiber cloth layer and an anti-wear topcoat layer in sequence from bottom to top, the surface of the anti-wear topcoat layer forming a smooth surface, the high-elastic primer layer being used for buffering the glass fiber cloth layer through local deformation when the substrate shrinks or expands, thereby avoiding wrinkling or delamination of the glass fiber cloth layer caused by deformation of the substrate.
[0007] In the aforementioned wooden floor heating floor based on the surface modification process for UV aging resistance, the high elastic primer layer is formed by sequentially coating two layers of high elastic primer monolayers, and the coating amount of each layer of high elastic primer monolayer is 10-30g / m 2 .
[0008] In the aforementioned wooden floor heating floor based on the surface modification process for UV aging resistance, an adhesion primer layer and a high-definition hardness primer layer are sequentially coated between the substrate and the high-elasticity primer layer from the inside to the outside.
[0009] In the aforementioned wooden floor heating floor based on the surface modification process for UV aging resistance, the coating amount of the adhesion primer layer is 10 to 30 g / m 2 The high-definition hardness primer layer is formed by sequentially coating three layers of high-definition hardness primer monolayers, and the coating amount of each layer of high-definition hardness primer monolayer is 20-30g / m 2 .
[0010] In the aforementioned wooden floor heating floor based on the surface modification process for UV aging resistance, a wear-resistant primer layer is provided between the glass fiber cloth layer and the wear-resistant topcoat layer.
[0011] In the aforementioned wooden floor heating floor based on UV aging resistance surface modification process, the surface of the glass fiber cloth layer is provided with a photocurable resin impregnation layer, which is used to adhere the glass fiber cloth layer to the high elastic primer layer and provide a bonding interface for the wear-resistant primer layer, so that the wear-resistant primer layer is separated from the glass fiber cloth layer and the high elastic primer layer after coating.
[0012] In the aforementioned wooden floor heating floor based on the surface modification process of UV aging resistance, the wear-resistant primer layer is formed by sequentially coating three layers of wear-resistant primer single layers, and the coating amount of each wear-resistant primer single layer is 10-30g / m 2 The coating amount of the anti-wear topcoat layer is 5 to 10 g / m 2 .
[0013] In the aforementioned wooden floor heating floor based on the surface modification process for UV aging resistance, the glass fiber cloth layer is paved with medium-alkali glass fiber cloth, and the thickness of the glass fiber cloth layer is 0.05-0.2 mm.
[0014] Compared with the prior art, the utility model has the following characteristics:
[0015] (1) The utility model provides a high elastic primer layer on the inner side of the glass fiber cloth layer, so that when the floor shrinks or expands, the high elastic primer layer can be used for buffering, that is, the inner side of the high elastic primer layer deforms together with the floor, and the outer side of the high elastic primer layer is restricted by the glass fiber cloth layer and remains in its original state, thereby utilizing the local deformation of the high elastic primer layer itself to adapt to the dimensional changes on both sides of the inner and outer sides, thereby preventing the floor from transmitting the lateral deformation to the glass fiber cloth layer and causing the glass fiber cloth layer to wrinkle or delaminate, thereby improving the structural stability and service life of the floor;
[0016] (2) By providing a light-curing resin impregnation layer on the surface of the glass fiber cloth layer, the glass fiber cloth layer can be wrapped from the outside, so that on the one hand, the mesh holes in the glass fiber cloth layer can be filled to provide a bonding interface for the subsequent coating and leveling of the wear-resistant primer layer; on the other hand, the light-curing resin impregnation layer can also fix the glass fiber cloth layer after curing, so that the glass fiber cloth layer maintains the fixed state unchanged and limits the high elastic primer layer, so that the high elastic primer layer forms a local deformation after being subjected to the deformation force of the substrate, that is, a buffering effect is achieved;
[0017] (3) Through the above-mentioned coordination, the utility model can stably lay the medium-alkali glass fiber cloth on the floor surface, thereby effectively improving the light aging resistance and flame retardancy of the floor and ensuring the stability of the floor in use;
[0018] (4) Through the structural coordination of the high-hardness primer layer, the glass fiber cloth layer, the wear-resistant primer layer and the wear-resistant topcoat layer, the overall impact resistance, wear resistance, light aging resistance, flame retardancy and the bonding performance between the paint film and the wood part of the paint film can be improved, so that the wear resistance of the utility model reaches 0.041g / 100r, the impact resistance is 12mm, the paint film hardness is 5H, and the cigarette burn resistance level is 2, that is, the physical and chemical properties of the floor after the glass fiber cloth is laid are guaranteed;
[0019] Therefore, the utility model can realize the stable laying of the glass fiber cloth on the surface of the wooden floor, and prevent the glass fiber cloth from wrinkling and delamination caused by deformation of the floor substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic diagram of the structure of the utility model in a normal state;
[0021] Figure 2 It is a schematic diagram of the structure of the utility model when the substrate is in a dry and shrunk state;
[0022] Figure 3 is a surface state diagram of comparative example 1 after testing in experimental example 1;
[0023] Figure 4 is a surface state diagram of comparative example 2 in experimental example 1 after testing;
[0024] Figure 5 is a surface state diagram of comparative example 1 in experimental example 3 after testing;
[0025] Figure 6 is a surface state diagram of comparative example 2 in experimental example 3 after testing;
[0026] Figure 7 is a surface state diagram of comparative example 3 after testing in experimental example 3;
[0027] Figure 8 is a surface state diagram of comparative example 1 in experimental example 4 after testing;
[0028] Fig. 9 This is a surface state diagram of comparative example 2 in experimental example 4 after testing.
[0029] The markings in the attached drawings are: 1-substrate, 2-high elastic primer layer, 3-fiberglass cloth layer, 4-wear-resistant topcoat layer, 5-adhesion primer layer, 6-high hardness primer layer, 7-wear-resistant primer layer, 8-light-curing resin impregnation layer. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.
[0031] Embodiment. A wooden floor heating floor based on a surface modification process for UV aging resistance is composed of Figure 1 As shown, it includes a substrate 1, and a high-elastic primer layer 2, a glass fiber cloth layer 3 and an anti-wear topcoat layer 4 are sequentially arranged on the surface of the substrate 1 from bottom to top. The glass fiber cloth layer 3 is paved with medium-alkali glass fiber cloth, and a number of fine meshes are evenly distributed on the glass fiber cloth layer 3. The thickness of the glass fiber cloth layer 3 is 0.05mm. The surface of the anti-wear topcoat layer 4 forms a smooth surface. The high-elastic primer layer 2 is used to buffer the glass fiber cloth layer 3 through local deformation when the substrate 1 shrinks or expands, so as to avoid wrinkling or delamination of the glass fiber cloth layer 3 caused by deformation of the substrate 1.
[0032] The flexibility of the paint film of the high elastic primer layer 2 needs to be controlled to be no more than 1 mm in diameter according to the measurement standard of GB / T1731-2020. Specifically, the 128804511 type high elastic primer of Jiangsu Haitian Technology Co., Ltd. can be used. The high elastic primer layer 2 is formed by coating two layers of high elastic primer monolayers in sequence, and the coating amount of each layer of high elastic primer monolayer is 20 g / m 2 , each coat was cured individually and polished using a 400 grit sanding belt.
[0033] An adhesion primer layer 5 and a high-definition hardness primer layer 6 are sequentially coated between the substrate 1 and the high-elasticity primer layer 2 from inside to outside. The high-definition hardness primer layer 6 can be formed by coating with FG-129200 high-definition hardness paint produced by Jiangsu Haitian Technology Co., Ltd.
[0034] The coating amount of the adhesion primer layer 5 is 20 g / m 2 The adhesion primer layer 5 is fully cured after coating and then polished with a 400-mesh sand belt; the high-definition hardness primer layer 6 is formed by sequentially coating three layers of high-definition hardness primer monolayers, and the coating amount of each layer of high-definition hardness primer monolayer is 25g / m 2 , each layer of HD hardness primer is cured individually after application and polished using a 400 grit sanding belt.
[0035] A wear-resistant primer layer 7 is provided between the glass fiber cloth layer 3 and the wear-resistant topcoat layer 4. After coating, the wear-resistant primer layer 7 levels the inner glass fiber cloth layer 3 so that the surface of the wear-resistant primer layer 7 forms a smooth surface.
[0036] The surface of the glass fiber cloth layer 3 is provided with a light-curing resin impregnation layer 8, which is used to adhere the glass fiber cloth layer 3 to the high elastic primer layer 2 and provide a bonding interface for the wear-resistant primer layer 7, so that the wear-resistant primer layer 7 is separated from the glass fiber cloth layer 3 and the high elastic primer layer 2 after coating, thereby improving the bonding effect of the wear-resistant primer layer 7 after coating;
[0037] When processing the light-curing resin impregnation layer 8, firstly, the surface of the high elastic primer layer 2 is pressed at 30g / m 2 The first layer of film-forming photocurable resin is coated with a coating amount of 100 g / m2, and then the glass fiber cloth is laid flat on the surface of the high elastic primer layer 2, and the glass fiber cloth is rolled with an elastic rubber roller at a pressure of 50 Pa-150 Pa to make the glass fiber cloth close to the high elastic primer layer 2 under the rolling action and eliminate the bubbles between the glass fiber cloth and the high elastic primer layer 2, and then the film-forming photocurable resin is cured; after the first layer of film-forming photocurable resin is cured, a 30 g / m2 film-forming photocurable resin is applied on its surface. 2 A second layer of film-forming photocurable resin is coated with a coating amount and cured, so that the first layer of photocurable resin and the second layer of photocurable resin wrap the glass fiber cloth from the outside after curing, that is, a photocurable resin impregnation layer 8 is formed; the film-forming photocurable resin can choose K-3022 film-forming photocurable resin glue.
[0038] The wear-resistant primer layer 7 is formed by sequentially coating three layers of wear-resistant primer, and the coating amount of each wear-resistant primer layer is 20g / m 2 Each wear-resistant primer layer is cured separately after coating and polished with a 400-mesh sandpaper; the coating amount of the wear-resistant topcoat layer 4 is 10 g / m 2The anti-wear topcoat layer 4 is completely cured after coating, and the anti-wear topcoat is polished using a 400-mesh sand belt.
[0039] Working principle of the utility model: The utility model sets a high elastic primer layer 2 on the inner side of the glass fiber cloth layer 3, and sets the coating amount of the high elastic primer layer 2 and the flexibility of the paint film, so that the inner side and the outer side of the high elastic primer layer 2 can change with the size of the substrate 1 and the glass fiber cloth layer 3 respectively. When the substrate 1 shrinks and expands, the inner side of the high elastic primer layer 2 can shrink and expand together with the substrate 1, and the outer side of the high elastic primer layer 2 can keep its size unchanged under the restriction of the glass fiber cloth layer 3, thereby playing a buffering effect, avoiding the glass fiber cloth layer 3 from being directly subjected to the lateral deformation force exerted by the substrate and wrinkling or delamination, and improving the structural stability of the glass fiber cloth layer 3 after paving.
[0040] On this basis, by providing a light-curing resin impregnation layer 8 on the outside of the glass fiber cloth layer 3, the glass fiber cloth layer 3 can be cured, which can improve the overall bonding strength and impact resistance of the paint film on the one hand, and on the other hand, it can also improve the deformation resistance of the glass fiber cloth layer 3. Therefore, when the glass fiber cloth is subjected to the deformation force from the high-elastic primer layer 2, it can keep its own structure unchanged and limit the surface of the high-elastic primer layer 2, so that the high-elastic primer layer 2 will only form local deformation after the substrate 1 shrinks and expands, thereby ensuring the paving stability of the glass fiber cloth layer 3.
[0041] Experimental Example 1: This experiment uses two wooden boards of the same size and material as substrates, and processes the two substrates to obtain comparative examples 1 and 2, respectively. Comparative example 1 is based on the wooden floor heating floor in the embodiment and removes the high elastic primer layer 2, glass fiber cloth layer 3 and light-cured resin impregnation layer 8 on the surface of the substrate; comparative example 2 is the wooden floor heating floor in the embodiment. Then, the impact resistance of the two groups of comparative examples was tested using the test standard in GB / T18102-2020 "Impregnated Paper Laminated Wood Floor" (steel ball 42.8mm diameter, 1.75m height).
[0042] Test results such as Figure 3 and Figure 4 As shown, Figure 3 This is the surface status diagram of comparative example 1 after the test. The thickness of the mark on comparative example 1 after the impact of the steel ball is 14 mm, and a large number of obvious cracks appear on the paint film on the floor surface, indicating that the paint film conventionally set on the floor surface will have obvious crack problems after being impacted by a heavy object. Figure 4 This is the surface status diagram of Example 2 after the test. The thickness of the mark on Example 2 after the impact of the steel ball is 12 mm, and the cracks on the floor surface are shallow, indicating that the glass fiber cloth can reinforce the paint film on the floor surface after paving and alleviate the deformation and rupture of the paint film after the impact.
[0043] Experimental Example 2: In this experimental example, the paint film surface wear resistance test was carried out on the wooden floor heating floor in the embodiment according to the national standard GB / T15036.1-2018. The test result showed that the wear resistance parameter of the floor surface was 0.041g / 100r, which is only half of the standard requirement.
[0044] This experimental example also conducted a paint film hardness test on the wooden floor heating floor in accordance with the national standard 15036.1-2018. The test result was a paint film hardness of 5H, which is higher than the hardness requirement of ≥H in the standard.
[0045] Experimental Example 3: This experiment uses three wooden boards of the same size and material as substrates, and processes the three substrates to obtain Comparative Example 1, Comparative Example 2 and Comparative Example 3 respectively; Comparative Example 1 is based on the wooden floor heating floor in the embodiment and removes the high elastic primer layer 2 on the floor surface; Comparative Example 2 is based on the wooden floor heating floor in the embodiment and only applies a single layer of high elastic primer on the surface of the high hardness primer layer 6, and the coating amount is 20g / m 2 ; Comparative Example 3 is the wooden floor heating floor in the embodiment.
[0046] Then the three groups of comparative examples were placed in an oven at 60°C to simulate the geothermal environment, and the glass fiber cloth morphology on the surface of the three groups of comparative examples was observed after 24 hours. Figure 5-7 As shown, Figure 5 This is a surface state diagram of comparative example 1. In the diagram, the fiberglass cloth on the floor surface forms dense and continuous wrinkles after the test, indicating that the existing method of directly laying the fiberglass cloth on the floor surface will cause the fiberglass cloth to wrinkle or delaminate as the substrate shrinks and expands. Figure 6 This is the surface state diagram of comparative example 2. In the figure, the glass fiber cloth on the floor surface has several white dots or lines after the test, indicating that the glass fiber cloth also has wrinkles or delamination in this area and cannot completely overcome the impact caused by the shrinkage and expansion of the substrate. Figure 7 This is a surface state diagram of comparative example 3. It can be seen from the diagram that the utility model can effectively avoid wrinkling or stratification problems on the surface of the glass fiber cloth by setting a high-elastic primer, thereby achieving the stability and service life of the glass fiber cloth after paving.
[0047] Experimental Example 4: Using Comparative Example 1 and Comparative Example 2 in Experimental Example 1 as samples, the two groups of samples were subjected to 12 hours of xenon lamp aging treatment, and the lower half of the floor was shielded with opaque material during the treatment. Figure 8-9 As shown, Figure 8 This is the surface status diagram of comparative example 1 after the test. From the picture, it can be seen that the upper and lower parts of comparative example 1 after the light aging test form an obvious contrast between light and dark, indicating that the surface of a conventional floor without medium-alkali glass fiber cloth will have a discoloration problem after long-term light exposure. Fig. 9This is a surface state diagram of comparative example 2 after the test. From the picture, it can be seen that the upper and lower parts of comparative example 2 after the light aging test are basically the same in color, and there is no obvious difference in light and dark, which shows that the utility model can improve the anti-light aging performance of the floor by laying the medium-alkali glass fiber cloth on the surface of the floor.
Claims
1. A wooden floor heating floor based on a surface modification process for UV aging resistance, characterized in that: The invention comprises a substrate (1), wherein a high elastic primer layer (2), a glass fiber cloth layer (3) and an anti-wear topcoat layer (4) are sequentially arranged on the surface of the substrate (1) from bottom to top, wherein the surface of the anti-wear topcoat layer (4) forms a smooth surface, and the high elastic primer layer (2) is used to cushion the glass fiber cloth layer (3) through local deformation when the substrate (1) shrinks or expands, thereby preventing the glass fiber cloth layer (3) from wrinkling or delamination due to deformation of the substrate (1).
2. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 1 is characterized in that: The high elastic primer layer (2) is formed by sequentially coating two layers of high elastic primer monolayers, and the coating amount of each layer of high elastic primer monolayer is 10-30 g / m 2 .
3. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 1 is characterized in that: An adhesion primer layer (5) and a high-hardness primer layer (6) are sequentially coated between the substrate (1) and the high-elasticity primer layer (2) from the inside to the outside.
4. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 3 is characterized in that: The coating amount of the adhesion primer layer (5) is 10 to 30 g / m 2 The high-definition hardness primer layer (6) is formed by sequentially coating three layers of high-definition hardness primer monolayers, and the coating amount of each layer of high-definition hardness primer monolayer is 20-30 g / m 2 .
5. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 1 is characterized in that: A wear-resistant primer layer (7) is provided between the glass fiber cloth layer (3) and the wear-resistant topcoat layer (4).
6. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 5 is characterized in that: The surface of the glass fiber cloth layer (3) is provided with a light-curing resin impregnation layer (8), which is used to adhere the glass fiber cloth layer (3) to the high-elastic primer layer (2) and provide a bonding interface for the wear-resistant primer layer (7), so that the wear-resistant primer layer (7) is separated from the glass fiber cloth layer (3) and the high-elastic primer layer (2) after coating.
7. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 5 is characterized in that: The wear-resistant primer layer (7) is formed by sequentially coating three layers of wear-resistant primer monolayers, and the coating amount of each wear-resistant primer monolayer is 10-30 g / m 2 The coating amount of the anti-wear topcoat layer (4) is 5 to 10 g / m 2 .
8. The wooden floor heating floor based on the surface modification process for UV aging resistance according to claim 1 is characterized in that: The glass fiber cloth layer (3) is formed by paving medium-alkali glass fiber cloth, and the thickness of the glass fiber cloth layer (3) is 0.05-0.2 mm.
Citation Information
Cited By
Ultraviolet-aging-resistant surface modification process and wooden ground heating floor
CN118288657A